Factors Related to Nurses' Moral Distress in the Era of the COVID-19 Pandemic: A Literature Review - Siti Zulaihah; Harmayetty Harmayetty; Tiyas Kusumaningrum (Universitas Airlangga, 2022)
Introduction: The global COVID-19 pandemic posed challenges to healthcare systems and professionals with the potential moral distress. The purpose of this review was to describe the risk factors associated with the moral distress of nurses in the era of the COVID-19 pandemic. Methods: The search for literature review articles was carried out in three databases (Scopus, Science Direct, and PubMed) with a publication span of 2019-2020. The PRISMA checklist was used to guide this review. Analysis and data tabulation were carried out in the article. Title, abstract, full-text and methodology were assessed to determine study eligibility. Result: A total of eight studies that fit the inclusion criteria were discussed based on internal and external factors of the risk of moral distress by nurses. Internal factors for the risk of nurses' moral distress include experience, decision making, perceptions of job dissatisfaction, patient care, coping with maladaptive strategies, failure to successfully care for patients, and limitations in take action. External factors for the risk of moral distress for nurses include lack of teamwork, unfavorable work environment and situations, conflicts of interest, excessive work demands, lack of resources, and loss of control over work situations. Conclusion: The risk factors for nurses' moral distress can be explained based on internal and external factors. The experience of nurses is important in dealing with the COVID-19 pandemic because this pandemic is a new disease and no treatment has yet been found, so other factors are associated with experience.